STRATEGI GURU PENDIDIKAN AGAMA KRISTEN DALAM MENANGANI BULLYING PADA SISWA KELAS XI DI SMK NEGERI 3 TANA TORAJA - Asriani Bine'; Selprianti Parapasan; Yelsi Embong Bulan; Krisdayanti Betri Mule; Meli Takke (CV. Adiba Aisha Amira, 2023)
The purpose of this research is how the PAK teacher's strategy is in dealing with bullying in class XI students at SMKN 3 Tana Toraja. Bullying is a form of action or violence that is carried out by someone intentionally or consciously to oppress weak people which can damage the victim's mentality and make the victim feel helpless and affect their academic achievement because there are threats faced by the victim of bullying. This study aims to determine the strategies of PAK teachers in dealing with bullying in class XI students at SMK Negeri 3 Tana Toraja. The research method used is qualitative research, with data collection methods through literature study and interviews. The informants are PAK teachers, perpetrators and victims of bullying. The PAK teacher's strategy in dealing with bullying in class XI students at SMK Negeri 3 Tana Toraja is to advise, give warnings and punish.